Ocorrência natural de micotoxinas em milho (Zea mays L.) e sua influência no desempenho de frangos de corte - Oliveira, Maurício Schneider (2014)
Fungi can be found everywhere in nature and are known occur in maize. Those which have the ability to produce substances toxic to humans and animals, from its secondary metabolism, are named toxigenic fungi and the metabolites produced are called mycotoxins. Due to the presence of various toxigenic fungal species in maize crop, the occurrence of a large number of metabolites is expected. Besides occur in native forms, mycotoxins can occur in the form called masked, a result of changes in structure or chemical reactions with constituents of plants, making them undetectable to the analytical methodologies conventionally employed. Due to the damage that mycotoxins can cause to human and animal health, laws establishing maximum permitted levels of contamination in food has been proposed, but restricted to a small number of mycotoxins, partly due to analytical limitations and partly in consequence of the lack of database of natural occurrence of these contaminants in the native and masked forms. To evaluate the occurrence of fungal metabolites in maize, 148 samples were collected in the South region of Brazil. All samples were contaminated with at least 10 fungal metabolites and the higher co-occurrence detected in the same sample was 51 metabolites. In all maize samples analyzed were detected at least two mycotoxins adressed by Brazilian law (fumonisin B1 and fumonisin B2). Besides the research of the native forms of mycotoxins, analysis for masked fumonisin were performed. Seventy two maize samples were analyzed and masked fumonisin concentration was found up to two times greater than the concentration of fumonisins in native form. Furthermore, a positive correlation (R = 0.97) was found between the concentration of native and masked fumonisin. Based on this correlation, a mathematical prediction model to estimate the concentration of total fumonisins, based on the concentration of native fumonisins was generated. After knowing the co-occurence of several fungal metabolites in maize, the performance of broilers chickens submitted to diets with fungal culture material was evaluated. Body weight and feed conversion were significantly altered after 21 days of experiment in the group receiving diet containing higher concentrations of fusaric acid. The analytical methodologies enabled a first approach to study the co-occurrence of mycotoxins in their native and masked forms in maize naturally contaminated, collected in the South region of Brazil. The negative effect on the performance of broilers chickens, demonstrating that the co-occurrence of Fusarium mycotoxins have real impact in poultry and requires greater attention of the parties involved.